Estudo da classificação e segregação do leite cru com ênfase na produção de queijo muçarela - Moraes, Mauricio Radaelli (2018)
Milk is the primary source of calcium for human consumption and has high nutrient density. Brazil, the world's fourth-largest milk producer, processed 35 billion tons in 2016. The milk received for industrial processing is not homogeneous. The characteristics of this raw material significantly influence the yield during the manufacture of dairy products. The central theme of this investigation is the allocation of the ‘right milk’ for each dairy product, especially in cheese processing. The principal factor to manufacture mozzarella cheese is the casein content. This work has a principal objetive, improving quality and yield in the production of mozzarella cheese, by of the analysis of the casein content and prioritization of raw milk destined for this process. Firstly, through a systematic review of the literature on the milk production chain, we present the quality aspects involved, and the intrinsic factors of the raw milk that influence yield in cheese production. Then, through a case study developed in a cooperative company, a model for the allocation of raw milk in a multi-product dairy industry was built based on the analysis of the casein content and focus on the optimization of the production of mozzarella cheese. To do so, it was necessary to know the profile of the casein content of all raw milk received by the dairy processing industry. After three months of data collection, the casein profile of the milk received was established from 15,236 samples analyzed and from this profile a strategy of segregation of the raw milk to be used in the production process of mozzarella cheese was defined. This new strategy of segregation offered an estimated theoretical gain power calculated in annualized R $ 3,700,000.00. Based on the implementation of the segregation strategy, a practical evaluation of direct potential gain were made that offered the company the possibility of increasing its revenue of R$ 5.912.820.00. In order to fully implement the segregation strategy, it is necessary to make investments in infrastructure. The investment plan was evaluated through a deterministic approach that resulted in an investment valuation with high return ((VPL R$ 14.153.166,39), low risk (Payback – Three months) and low sensitivity (TMA variation 5,900%). It was also evaluated through a stochastic approach through Monte Carlo Simulation with 10,000 and 100,000 simulations which has returned a highly profitable and exciting investment for the industry. The study of improvements through the physical-chemical profile of milk is a fruitful field for future research with practical implications for multiproducts companies of the dairy sector.